Analisis Performa Kendaraan Konversi Internal Combustion Engine (ICE) Menjadi Kendaraan Listrik - ANJABTUKO, DZAKWAN AVRILDETZA; Ramdhani, S.Pd., M.Eng. (Pengelolaan Penerbitan Publikasi Ilmiah (P3I) Politeknik Negeri Madiun, 2025)
The transition from Internal Combustion Engine (ICE) vehicles to electric-powered alternatives is recognized as a crucial initiative to support environmentally sustainable transportation systems and reduce greenhouse gas emissions. This study focuses on assessing the performance and suitability of a Permanent Magnet Synchronous Motor (PMSM) as the primary drive mechanism in a vehicle retrofitted from an ICE-based system. A combination of literature analysis, field inspections, and technical evaluations was employed to examine several key parameters, including motor output, battery capacity and resilience, projected driving distance, and required charging time. Test results indicate that the PMSM produced a torque of 110 Nm and a power output of 70.45 PS—slightly lower than the original ICE engine’s torque of 118.6 Nm and 86 PS of power. The 15.85 kWh LiFePO₄ battery demonstrated exceptional energy efficiency at 98%, supporting a continuous operational time of 1.55 hours and a travel range of approximately 42.6 kilometers. Charging the battery to full capacity took about 1.29 hours. While a modest decline in power output was observed compared to the ICE system, the electric drivetrain exhibited high efficiency and consistent performance. These empirical findings serve as a valuable reference for advancing the implementation of effective and practical electric vehicle conversion technologies in future mobility solutions.